Retrospective analysis of systemic chemotherapy and total parenteral nutrition for the treatment of malignant small bowel obstruction. (29th December 2015) - Chouhan, Jay; Gupta, Rohan; Ensor, Joe; Raghav, Kanwal; Fogelman, David; Wolff, Robert A.; Fisch, Michael; Overman, Michael J.
Abstract: Malignant small bowel obstruction (MSBO) that does not resolve with conservative measures frequently leaves few treatment options other than palliative care. This single‐institution retrospective study assesses the outcomes of a more aggressive approach—concurrent systemic chemotherapy and total parenteral nutrition (TPN)—in the treatment of MSBO. The MD Anderson pharmacy database was queried to identify patients who received concurrent systemic chemotherapy and TPN between 2005 and 2013. Only patients with MSBO secondary to peritoneal carcinomatosis requiring TPN for ≥8 days were included. Survival and multivariate analyses were performed using the Kaplan–Meier method and Cox proportional hazard models. The study included 82 patients. MSBO resolution was observed in 10 patients. Radiographic assessments showed a response to chemotherapy in 19 patients; 6 of these patients experienced MSBO resolution. Patients spent an average of 38% of their remaining lives hospitalized, and 28% of patients required admission to the intensive care unit. In multivariate modeling, radiographic response to chemotherapy correlated with MSBO resolution (odds ratio [OR] 6.81; 95% confidence interval [CI], 1.68–27.85, P = 0.007). Median overall survival (OS) was 3.1 months, and the 1‐year OS rate was 12.6%. Radiographic response to chemotherapy (HR 0.30; 95% CI, 0.16–0.56, P < 0.001), and initiation of new chemotherapy during TPN (HR 0.55; 95% CI, 0.33–0.94, P = 0.026) independently predicted for longer OS. Concurrent treatment with systemic chemotherapy and TPN for persistent MSBO results in low efficacy and a high morbidity and mortality, and thus should not represent a standard approach. Abstract : Malignant small bowel obstruction (MSBO) represents a vexing clinical situation for practicing clinicians as cases where surgery is not appropriate lead to a supportive care and hospice approach. Though the role of total parenteral nutrition (TPN) alone has been investigate in malignant bowel obstruction the aggressive role of TPN combined with chemotherapy has not. This manuscript represents the first large dataset to address this question and provide actual data to the inevitable theoretical potential of providing a patient with MSBO TPN and systemic chemotherapy. In this report, we described outcomes of a population diagnosed with MSBO in the setting of peritoneal carcinomatosis.